Pelatihan Pengelolaan Keuangan Sederhana untuk Pedagang Asongan Binaan TBM PKBM Sakila Kerti di Terminal Tipe A Tegal - Irwan Prasetyo; Dewi Indriasih; Dien Noviany Rahmatika; Jaka Waskito; Juli Riyanto Tri Wijaya; Muhammad Andi Budiyanto; Bei Harira Irawan (Fokus ABDIMAS, 2026)
Simple Financial Management Training for street vendors assisted by the Sakila Kerti Community Service Center (PKBM) at the Tegal Type A Terminal was conducted as a form of community service aimed at improving vendors' ability to manage business finances in a more organized, transparent, and effective manner. Street vendors generally still face various obstacles, such as the lack of separation between business and household finances, inadequate recording of daily transactions, and a limited understanding of business planning. Through this training, participants were equipped with basic knowledge and skills regarding recording incoming and outgoing cash, preparing simple reports, and financial planning for business sustainability. The methods used included surveys, outreach, hands-on recording practice, and evaluation through pre- and post-tests to measure the training's effectiveness. The training results showed an increase in participants' understanding of the importance of business financial management, their ability to prepare simple financial reports, and their awareness of separating personal and business finances. Thus, this training successfully improved basic financial literacy among street vendors, thus providing an important foundation for the sustainable development of micro-enterprises.